Remote monitoring system for maize seeding parameters based on Android and wireless communication - Xie, Chunji; Zhang, Dongxing; Yang, Li; Cui, Tao; Zhong, Xiangjun; Li, Yuhuan; Ding, Youqiang; Ding, Zhengliang (International Journal of Agricultural and Biological Engineering, 2020)
Most traditional maize seeding parameter monitoring devices use wired data transmission. The problems include wiring troubles, short transmission distances. And human-computer interaction display terminals are unique and usually customized rather than universal. A remote monitoring system for maize seeding parameters based on Android and wireless communication was developed in this study. The system used a single-chip microcomputer as the main controller and an infrared photoelectric sensor to capture seed information. The Android terminal application was used to set and display the seeder’s seed parameter information and monitor it. The Air202 communication module enabled remote data transmission, while the Global Positioning System (GPS) monitored the speed of the planter. By establishing a message queue telemetry transmission (MQTT) cloud served as a data freight station, data reception, storage and forwarding can be performed. Seeding parameters can generate Excel spreadsheets in real-time for easy data processing and storage. In order to verify the reliability of the system, the seeding parameter monitoring comparison test and the multi-terminal remote monitoring test were designed. The results of the seeding parameter monitoring comparison test showed that the monitoring system of this study had higher monitoring accuracy. The maximum average relative error of seeding parameter monitoring was 0.4%, which had high monitoring accuracy. The multi-terminal remote monitoring test showed that the monitoring system of this research can adapt many types of Android terminals, realize the wireless connection, and realize remote synchronous monitoring at different distances. This study provides a reference for intelligent remote monitoring and intelligent agriculture on unmanned farms.Keywords: remote monitoring system, maize seeding parameters, Android and wireless communication, remote synchronous monitoring, intelligent agricultureDOI: 10.25165/j.ijabe.20201306.5485Citation: Xie C J, Zhang D X, Yang L, Cui T, Zhong X J, Li Y H, et al. Remote monitoring system for maize seeding parameters based on Android and wireless communication. Int J Agric & Biol Eng, 2020; 13(6): 159–165.